2022
DOI: 10.1039/d2fo01713j
|View full text |Cite
|
Sign up to set email alerts
|

Identification of linear epitopes and their major role in the immunoglobulin E-binding capacity of tropomyosin from Alectryonella plicatula

Abstract: The allergen TM was purified from Alectryonella plicatula; the sequence was cloned. Linear epitopes played a major role in IgE-binding capacity of ATM. Nine linear epitopes were verified. L-ATM-2 was the key epitope to bind with IgE; L-ATM-5 and L-ATM-7 were most conservative in shellfish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Combined with the goat anti-Atlantic cod extract sera IgG immunoblotting results in Figure B, the epitopes of these fish allergens were also hydrolyzed after 60 h of fermentation. However, since the linear epitopes of these allergens were not identified, the immunoinformatics tools were used to help us predict them and the results are shown in Table S1. , After data screening, the linear epitopes identified by using myosin light chain 1 and creatine kinase as examples are shown in Table S2, namely, M-01 to M-10 and C-01 to C-12, respectively. The fermentation process of strain Lh191404 destroyed the linear epitopes of allergens after exposure, resulting in decreased allergenicity, which was consistent with the partial results of antigenicity in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Combined with the goat anti-Atlantic cod extract sera IgG immunoblotting results in Figure B, the epitopes of these fish allergens were also hydrolyzed after 60 h of fermentation. However, since the linear epitopes of these allergens were not identified, the immunoinformatics tools were used to help us predict them and the results are shown in Table S1. , After data screening, the linear epitopes identified by using myosin light chain 1 and creatine kinase as examples are shown in Table S2, namely, M-01 to M-10 and C-01 to C-12, respectively. The fermentation process of strain Lh191404 destroyed the linear epitopes of allergens after exposure, resulting in decreased allergenicity, which was consistent with the partial results of antigenicity in this study.…”
Section: Resultsmentioning
confidence: 99%
“…In our laboratory, we prepared polyclonal antibodies specific to Haliotis discus hannai TM (HTM), Alectryonella plicatula TM (ATM), and Mimachlamys nobilis TM (MTM) using rabbit hosts. [15][16][17] Horseradish peroxidase (HRP)-conjugated goat antihuman IgE antibody and HRP-conjugated goat anti-rabbit IgG antibody were obtained from Abmart Company (Birmingham, Alabama, USA). Bovine serum albumin (BSA) and 8-anilino-1naphthalenesulfonic acid (ANS) were purchased from Sigma-Aldrich (St. Louis, Missouri, USA).…”
Section: Reagentsmentioning
confidence: 99%
“…15 Similarly, Ji et al identified TM in Haliotis discus hannai (ten positive serum samples) and Alectryonella plicatula (seventeen positive serum samples). 16,17 These studies conducted serological tests, which revealed that Haliotis discus hannai TM (HTM), Alectryonella plicatula TM (ATM), and Mimachlamys nobilis TM (MTM) are all major allergens in molluscs. However, no research has been carried out to investigate the relative strength of their allergenic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, chemical denaturants are used to study the relationship between the destruction of allergen structure and the change of IgG-/IgE-binding capacity. Meanwhile, hypoallergenic derivatives treated with denaturants could be used for allergen specific immunotherapy. Sodium dodecyl sulfate (SDS) changed the tertiary structures of protein molecules by destroying the hydrogen bonds and hydrophobicity of proteins . Dithiothreitol (DTT) and β-mercaptoethanol (β-Me) are typical disulfide bond reducing agents that can destroy the disulfide bond in protein.…”
Section: Introductionmentioning
confidence: 99%